Basil of Caesarea - Hildebrand, Stephen M., 1973- (Grand Rapids, MI. Baker Academic, 2014)
"This introduction to the thought of Basil of Caesarea surveys his theological, spiritual, and monastic writings, showing the importance of his work for contemporary theology and spirituality. It brings together various aspects of Basil's thought into a single whole and explores his uniqueness and creativity as a theologian. The volume engages specialized scholarship on Basil but makes his thought accessible to a wider audience."--From publisher description.
Awakenings : living the gospel at home and in the church -- Man : body and soul, "made" and "molded" -- The two books : creation and scripture -- The Trinity, simply : as we are baptized, so we believe -- The Trinity in controversy : against Eunomius and Eustathius -- Heavenly politeia : the basics of Christian discipleship -- The monastic life : from commandments to community -- Tradition and creativity : theology and asceticism -- Conclusion: Theology and spirituality in the thought of St. Basil.
Includes bibliographical references and index.
Keywords: Basil, -- Saint, Bishop of Caesarea, -- approximately 329-379.